Pengaruh Penggunaan Model Blended Learning Terhadap Hasil Belajar Siswa - Erni Nuraeni; Nur Ainiyah (Yayasan Sahabat Literasi Edukasi dan Publikasi Bandung, 2023)
This research was motivated by the learning outcomes of students under KKM. The purpose of this research is to determine the effect of using a blended learning model on student learning outcomes in PAI learning at SMA Pemuda Banjaran. This study used a quantitative approach descriptive method, data collection techniques using questionnaires and observation. Statistical Analysis i.e. Simple Linear Regression Analysis, Correlation Coefficient Analysis, Descriptive Statistical Analysis and Hypothesis Testing Test t. The results of this study show that the The blended learning model has an effect on student learning outcomes as evidenced by statistical calculations, the results were obtained that there was a significant influence and the level of strong relationship between Variable X and Variable Y was 49.98% and the remaining 50.02% was influenced by other factors